The concepts of morality in Islam and Buddhism : a comparative analysis on the personal code of ethics - Mohd. Rosmizi bin Abd. Rahman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
Today, moral decadence has become a serious global predicament. In one aspect, this problem is due to the fact that some people have left religion and faith behind, taking up secularism, liberalism, rationalism and empiricism as the substitution. Consequently, some people live and behave unethically and as a result violence, oppression, crime, exploitation, victimization and other problems, are spreading and enveloping almost the entire globe. However, in the ethical aspect, all religions, including Islam, Christianity, Hinduism and Buddhism, have provided ethical system and emphasis on moral life that is, all encourage good conduct and prohibit bad behaviour. Realizing the importance of this, therefore, this study seeks to uncover and analyse the fundamental ethics in two major religions, namely Islam and Buddhism. The study is limited to personal code of ethics in these two religions. In so doing, the personal code of ethics in these two living religions is highlighted, analysed and compared in several aspects. Since the comparative and analytical methods are used, therefore, this study involves mainly library research. In describing personal ethics, especially in Buddhism, both primary and secondary sources have been relied upon. From the study, several findings have been drawn. Generally, Islam and Buddhism share a lot of similarities and have mutual understanding on various aspects related to ethics, such as on the nature, the position, the significance and objectives of ethics in life. Moreover, the nature, the understanding and the items of personal code of ethics in the two religions are also similar. To conclude, both religions have provided personal codes of ethics which elucidate comprehensive and excellent guidelines on how to live morally and both religions agree that every man should observe and practise these personal ethics throughout his life.